A Neglected Acne Scar Type: Papular Acne Scars and Their Correlations With Keloid Scars. Issue 10 (October 2021) - Lee, Ye-Jin; Lee, Chan-Yang; Shin, Min Kyung
Abstract : BACKGROUND: Acne scarring can be divided into 2 types: atrophic and hypertrophic scars. Papular acne scars are commonly encountered, skin-colored papules on the chin and back. OBJECTIVE: This study aimed to estimate the prevalence of each acne scar type and to investigate the clinical manifestations of papular acne scars. METHODS: This retrospective study included 416 patients with acne scars. Dermatologists classified the scars into 3 types (atrophic, papular, and keloid type) based on clinical photographs and analyzed the clinical and histologic features of papular acne scars. RESULTS: Among 416 patients with acne scars, 410 patients (98.56%) had atrophic scars, 53 patients (12.74%) had keloid scars, and 46 patients (11.06%) had papular acne scars. Twenty patients (4.81%) had both papular and keloid acne scars. Histologic analysis showed fibrotic tissue in both keloid and papular acne scars. Fibrosis of the papular scar was limited to the upper dermis. CONCLUSION: Papular acne scars were significantly more prevalent in patients with keloid scars than in those without keloid scars. These results provide a basis for understanding papular acne scars, which have been under-recognized. The association between papular and keloid acne scars can suggest the decision for scar treatment.